An influence of giving compensation on employee performance in Balongan district office, Indramayu District - Fuadi, Afrian (Indonesia Research and Study Center, 2023)
The factor for decreasing employee performance in the Balongan District Office, Indramayu Regency, is the impact of giving inappropriate compensation to employees. With compensation can increase the effectiveness of work to achieve organizational goals of the company. Compensation is one of the operational functions in human resources that regulates wages/salaries and services provided by the company to its employees in return for what has been given to employees. This study uses the method of library research or literature review by comparing several previously published national journals. The results of this study reveal that motivation and compensation affect employee performance either partially or simultaneously.